New species of Latrunculia from the Agulhas shelf, South Africa, with designation of a type species for subgenus Biannulata (Demospongiae, Poecilosclerida, Latrunculiidae) - Samaai, Toufiek; Janson, Liesl; Kelly, Michelle (Zootaxa, 2012)
Three new species of Latrunculia are described from Algoa Bay, and Alphard and 45-Mile Banks, on the Agulhascontinental shelf off the southern coast of South Africa. Latrunculia gotzi sp. nov., from Alphard Banks, forms a thickraised pad with broad, low, meandering areolate porefields that are characteristically lighter in colour than the surroundingmahogany brown ectosome. Latrunculia kerwathi sp. nov., from 45-Mile Banks, forms a thin, dark greenish brownencrustation, with very small, discrete, crater-shaped porefields. Latrunculia algoaensis sp. nov., from Algoa Bay, is agreen hemisphere with relatively large, thick-lipped, circular areolate porefields. While the megascleres in these newspecies vary specifically in their dimensions, the former two species have small irregular spines on the styles. Theanisodiscorhabds of the new species also vary specifically in dimensions and degree of ornamentation, but have anundifferentiated basal whorl and manubrium, with only median and subsidiary whorls around the shaft. These are identicalin overall form to the anisodiscorhabds in several South African and New Zealand species currently recognised within thesubgenus Latrunculia (Biannulata) Samaai et al., 2006, a group of 13 species for which no type species was ever assigned. A type species is designated herein.